Lessons Learned From a Pilot RCT of Simultaneous Versus Delayed Initiation of Continuous Glucose Monitoring in Children and Adolescents With Type 1 Diabetes Starting Insulin Pump Therapy. (May 2014) - Olivier, Patricia; Lawson, Margaret L.; Huot, Celine; Richardson, Christine; Nakhla, Meranda; Romain, Judette
Uncertainty remains about effectiveness of continuous glucose monitoring (CGM) in pediatric type 1 diabetes (T1D). Success with CGM is related to CGM adherence, which may relate to readiness to make the behavior changes required for effective use. We hypothesize that readiness for change will be greater at initiation of insulin pump therapy than in established pump users, and that this will predict CGM adherence. Our objective was to evaluate the feasibility of a randomized controlled trial (RCT) in children with established T1D comparing simultaneous pump and CGM initiation to standard pump therapy with delayed CGM initiation. We randomized participants to simultaneous pump and CGM initiation or to standard pump therapy with the option of adding CGM 4 months later. CGM adherence was tracked via web-based download and readiness for change assessed with the SOCRATES questionnaire. Of 41 eligible children, 20 agreed to participate; 15 subjects completed the study (7 males; baseline age 11.8 ± 4.0 years; T1D duration 2.7 ± 2.7 years; mean A1C 8.2 ± 0.8%). Six of 8 simultaneous group subjects used CGM > 60% of the time for 4 months compared to 1 of 7 delayed group subjects ( P = .02). Using SOCRATES, we could assign 87-100% of subjects to a single motivation stage at baseline and 4 months. This pilot study demonstrates the feasibility of randomizing pump naïve children and adolescents with established T1D to simultaneous pump and CGM initiation versus standard pump therapy with delayed CGM initiation. Lessons from this pilot study were used to inform development of a full-scale multicenter RCT.